The Effect of Problem-Based Adaptive Learning on Students' Mathematical Concept Understanding Ability - Ramayani, Fitri; Lubis, Nur Ainun (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
The aim of this research is to find out whether there is a significant difference in the data on students' understanding of mathematical concepts with problem-based adaptive learning and conventional learning carried out at SMA Negeri 1 Pantai Labu. Class X students (n=150) were involved as research subjects as a population. Types of pseudo-experimental research with a quantitative approach. This research sample was taken using a stratified random sampling technique. The sample was divided into two groups, namely the experimental group consisting of 30 students who studied with Problem-Based Adaptive Learning and the control group consisting of 30 students who studied with conventional learning. This research is semi-experimental and the instrument is a concept understanding test. Data processing techniques include normality tests, homogeneity tests and independent sample t-tests with the help of the IBM SPSS Statistics 30 and Microsoft Excel programs. Based on the results of descriptive statistical tests, it was found that the average score for problem-based adaptive learning was 84.47 (SD=3,910) , while the average score for conventional learning was 89.40 (SD=2,513). The results of data analysis show that there is a significant difference between students who learn through problem-based adaptive learning and conventional learning, with a significance value of 0.12 > 0.05, which means H1 is accepted and H0 is rejected. So there is an influence of problem-based adaptive learning on the understanding of mathematical concepts of Class X students at SMA Negeri 1 Pantai Labu in the 2024/2025 academic year.